School Accreditation, Teachers’ Competence, and Students’ English Performance in South Sumatra - Retno Indri Yustika; Chuzaimah D. Diem; Ismail Petrus (Jurnal Bahasa dan Sastra, 2019)
Abstract: This study examined school accreditation, English teachers’ competence, and stu- dents’ English performance and the correlations among them. The samples of this study were 101 junior high schools and 280 English teachers in 16 regencies and cities in South Sumatra Province. This study analyzed the school accreditation as measured by 8 National Education Standards, English teachers’ competence by UKG (Teacher Competence Test), and students’ English performance by English National Examination results. The findings revealed that the schools accredited B dominated the results of accreditation (84.55) in which the standard of teachers and educational personnel had the lowest score, English teachers’ competence was barely average (51.96), and the students’ English performance (ENE results) was in the poor level (43.57). In general, there was no significant correlation between students’ English per- formance and the school accreditation as well as between students’ English performance and teachers’ competence in South Sumatra Province. However, a positive significant correlation was found between students’ English performance and school accreditation in Empat Lawang Regency and Palembang City. A positive significant correlation also existed between students’ English performance and teachers’ pedagogical competence in Banyuasin, Musi Banyuasin, and OKU Regencies.Keywords: students’ English performance, school accreditation, teachers’ competenceAbstrak: Studi ini meneliti akreditasi sekolah, kompetensi guru Bahasa Inggris, dan prestasi bahasa Inggris siswa dan korelasi di antara mereka. Sampel penelitian ini adalah 101 sekolah menengah pertama dan 280 guru bahasa Inggris di 16 kabupaten dan kota di Provinsi Sumatera Selatan. Studi ini menganalisis akreditasi sekolah yang diukur dengan 8 Standar Pendidikan Nasional, kompetensi guru bahasa Inggris dengan UKG, dan prestasi bahasa Inggris siswa melalui hasil Ujian Nasional Bahasa Inggris. Hasil studi ini mengungkapkan bahwa sekolah yang terakreditasi B mendominasi hasil akreditasi (84,55) dengan skor terendah untuk standar guru dan tenaga kependidikan, kompetensi guru bahasa Inggris hampir rata-rata (51,96), dan prestasi Bahasa Inggris siswa (UN) di tingkat rendah (43.57). Secara umum, tidak ada korelasi signifikan antara prestasi Bahasa Inggris siswa dan akreditasi sekolah serta antara prestasi Ba- hasa Inggris siswa dan kompetensi guru di Provinsi Sumatera Selatan. Namun, korelasi positif signifikan ditemukan antara prestasi Bahasa Inggris dan akreditasi sekolah di Kabupaten Em- pat Lawang dan Kota Palembang. Korelasi positif signifikan juga ditemukan antara prestasi Ba- hasa Inggris siswa dan kompetensi pedagogik guru di Kabupaten Banyuasin, Musi Banyuasin, dan OKU.Kata-kata Kunci: prestasi Bahasa Inggris siswa, akreditasi sekolah, kompetensi guru